The Play and Place of Criticism - Krieger, Murray (Johns Hopkins University Press, 2019)
Originally published in 1967. In The Play and Place of Criticism, Professor Krieger addresses basic questions related to criticism in the title essay that forms the introduction to this collection and that constitutes a considered statement of his "contextualist" position. In agreement with Spitzer, Krieger believes that the critic has a valuable part to play in relating the "new words" of the individual poem to the "old words" of the language. He goes further in identifying the role of the critic as essentially rhapsodic, a sharing-in and an expression of the poet's "fine frenzy," which, when it succeeds, transports the critic beyond words and dooms his analytical efforts to failure. Thus, while defending the critic's right to exercise "the free play of the mind" in approaching his subject, the author insists that the critic recognize his subordinate "place" in performing his act of mediation. Elsewhere in the volume Krieger uses other terms and metaphors to explore similar problems revolving around the mediate and the immediate in poetry and criticism. In calling for a poetry of "still movement," for example, he examines both the opposition and the union of temporal with spatial or plastically formal elements, of the dynamically empirical with the statically archetypal. Having defined his critical position in these ways, Krieger relates it to other schools of criticism and applies its methods to the analysis of works by Shakespeare, Pope, Arnold, Hawthorne, and others.